(untitled) (Research, Society and Development, 2022)
Community Health Agents (CHA) are essential for the work of Primary Health Care (PHC) to be successful, but they may encounter obstacles in their performance. The goal of the study was to understand the importance of Community Health Agents in the work of territorialization in the Municipality of Itaperuna-RJ. For this, an exploratory field research was carried out with the application of a questionnaire to the CHA of the municipality, respecting the ethical aspects recommended by Resolution 466/2012. The following inclusion criteria were established: CHA aged between 18 and 60 years and working in the CEHAB or Surubi communities. For exclusion: CHA who did not reside in the studied territory. Thus, 14 professionals participated in the study, with the following results predominating: they consider that the profession makes it possible to help the community (53.8%), but this help is limited (33.3%); carry out planning of their activities (83.3%); have already acquired diseases resulting from their work (86.7%), mainly Covid-19 (33.3%); have only elementary education (83.3%); the main factor that harms the professional relationship is misinformation (58.3%); the advantage of living and working in the same territory is the proximity (66.7%) and the disadvantage is the demand from the population outside working hours (41.7%). It was concluded that this professional is essential for the promotion of improvements, but there are several challenges, such as the fact that 50% CHA interviewed say that they did not receive the proper training.